Alternative Development Strategy for the Peruvian Economy - López Chau, Alfonso (2006)
This article is a reflection on development strategy that examines the crucial relationship between growth theories and the concept of globalization; on the other hand, it is a criticism of the current practice that privileges the fiscal deficit as a conceptual anchor of macroeconomic policy.